Efecto de La Ε-Polilisina y propóleo como conservantes en la vida útil del yogurt - Lectong Cusme, Nieve Esther (2020)
This study evaluated the effect of the different mixtures of ε-Polylysine and Propolis on the shelf life of yogurt, being an experimental research. Five treatments with mixtures of ε-polylysin and propolis were evaluated in a completely randomized design with 3 replicas. The behavior of the preservative mixtures on pH, acidity, counts of Escherichia coli, Staphylococcus aureus, and molds and yeasts, as well as the kinetic behavior of the physical and chemical properties of yogurt stored at a temperature of 4 °C for 30 days was studied. A significant decrease of pH was observed with preservatives, with the value of T4-T5 treatments (4.33±0.36) higher than T1-T2-T3 (4.06±0.21), which were considered more in compliance with international standards. No presence of E coli or S aureus was recorded. The shelf life of the product was calculated taking as an indicator the count of molds and yeasts, using the Labuza equation, being treatment 1 (5 mg ε-polylysine – 1 mL propolis) the one that allowed a longer shelf life (123 days). Tasting analysis was performed with 75 untrained panelists, who indicated that treatments 2 (10 mg ε-polylysine and 0.9 mL propolis) and 3 (15 mg ε-polylysine and 0,8 mL propolis) had the highest overall acceptability.